2018
DOI: 10.3892/mmr.2018.8522
|View full text |Cite
|
Sign up to set email alerts
|

Potential roles of AMP-activated protein kinase in liver regeneration in mice with acute liver injury

Abstract: Liver regeneration post severe liver injury is crucial for the recovery of hepatic structure and function. The energy sensor AMP‑activated protein kinase (AMPK) has a crucial role in the regulation of nutrition metabolism in addition to other energy‑intensive physiological and pathophysiological processes. Cellular proliferation requires intensive energy and nutrition support, therefore the present study investigated whether AMPK is involved in liver regeneration post carbon tetrachloride (CCl4)‑induced acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…The results revealed that both PCNA and VEGF levels were elevated in the liver tissues of mice injected with CCl 4 compared to normal mice. These outcomes are consistent with the previous published studies ( Huang et al, 2018 , Rahmani et al, 2019 , Mercado-Gómez et al, 2020 ). On the other hand, the increased levels of PCNA and VEGF were normalized after the treatment with the phthalimide analog.…”
Section: Discussionsupporting
confidence: 94%
“…The results revealed that both PCNA and VEGF levels were elevated in the liver tissues of mice injected with CCl 4 compared to normal mice. These outcomes are consistent with the previous published studies ( Huang et al, 2018 , Rahmani et al, 2019 , Mercado-Gómez et al, 2020 ). On the other hand, the increased levels of PCNA and VEGF were normalized after the treatment with the phthalimide analog.…”
Section: Discussionsupporting
confidence: 94%
“…Drug-induced toxicity causes hepatic injury in mice. CCl 4 is a direct hepatotoxin used widely in laboratories to induce acute liver disease because its biotransformation is catalyzed primarily by cytochrome P450s in hepatocytes [ 44 , 45 , 46 ]. The cytochrome P450-dependent metabolism of CCl 4 yields trichloromethyl radical (•CCl3) and trichloromethyl peroxyl radical (•CCl3OO) as major metabolites [ 47 ], which can lead to lipid peroxidation by reacting with membrane lipids and further oxidize other cellular components, including nucleic acids and protein, resulting in hepatocyte toxicity with the release of hepatic enzymes, such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP) and bilirubin [ 44 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…CCl 4 treatment contributes to metabolic dysfunction including lipid peroxidation, increasing ROS production [ 50 ]. Reactive metabolites produced from CCl 4 may cause radical stress and contribute to apoptosis, which may be responsible for hepatotoxicity and liver failure [ 45 ]. Hence, the CCl 4 exposure model is extremely close to mimicking the cellular environment in animals from oxidative stress to carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study reported increased AMPK activity in liver of rats with CCl 4 -induced liver injury within 24 h and suggested that AMPK could stimulate autophagy to maintain cellular homeostasis [38]. However, another study revealed that AMPK was primarily activated at the liver regeneration stage in mice with CCl 4 -induced liver injury, but not in early stage of liver injury [39]. In our study, AMP and two of its metabolites (e.g., adenosine and inosine) had lower levels in the model group than the control group.…”
Section: Resultsmentioning
confidence: 99%